(untitled) (Archives of Mechanics - Test, 2002)
The problem of motion of a beam-like elastic body along a horizontal plane in terms of friction, large displacements and finite strains will be considered. The equations of motion are derived using Gibbs-Appell approach. Deformations of the body and sliding velocity distribution are presented.